The German Cliometrics Database - Tobias A. Jopp; Mark Spoerer (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
This short article introduces the German Cliometrics Database as the foundation for an article by Jopp and Spoerer (2024) who trace cliometric research on German history. This newly constructed database of every publication that (1) contributes to the historiography of Germany and (2) employs, as a baseline, inferential statistics enables researchers to find cliometric studies related to their own work much more efficiently. Even though no full texts are provided alongside the data file, the collected abstracts or, respectively, summaries for every publication in the database allow for some baseline text mining approaches. Along with the remaining information provided, they may also form the basis for broader bibliometric or historiographical studies.
Keywords: B4; B16; C01; N01; 330; cliometrics; economic history; Germany; German history; quantitative history; social history